TRADITIONAL SAYINGS AS REFLEXES OF HOUSEHOLD, BARN, AND BYRE - Smith, John B. (Proverbium - Yearbook, 2012)
[...] (sic!) on of which can in turn add to our knowledge and under-standing of the sayings. This seems to be borne out by scrutiny of the saying to stick one’s spoon in the wall for “to die”, the literal meaning of which emerges from an examination of traditional eating habits and implements. Along with proverbialisms originating in the household, others that have grown out of the wider rural environment are dis-cussed. Although we proceed from English sayings, many of them dialectal, not a few of these have Continental counterparts, the study of which can cast further light, but also raise questions as to origin, development, and transmission.